HUBUNGAN PENGETAHUAN DAN SIKAP KEPALA KELUARGA TENTANG JAMINAN KESEHATAN NASIONAL (JKN) DENGAN KEPESERTAANNYA SECARA MANDIRI DI PUSKESMAS BANGKINANG KOTA - Rinda Fithriyana Fithriyana (Universitas Pahlawan, 2019)
JKN since its inception until now has reaped many problems, mainly due to lack of socialization. BPJS itself actually has conducted JKN socialization, but socialization from BPJS has not been maximized. This has caused many complaints from the poor. Until now there are still some parties who do not know JKN, as a result they also do not know the mechanism of JKN that uses a tiered and back referral system. The purpose of this study was to determine the relationship of knowledge and attitudes of the head of the family on National Health Insurance (JKN) with its participation independently in the work area of the Bangkinang City Health Center. This type of research design used is cross sectional study. The population in this study were all family heads who visited the City Bangkinag Health Center with a total sample of 84 people. Data analysis was performed univariately and bivariately with chi square test. The results of this study found there is a relationship between JKN membership independently with knowledge (pvalue = 0,000) and attitude (pvalue = 0,000). Researchers suggest that the results of this study can be used as a basis for policy making in an effort to increase JKN Mandiri membership to ensure the health of families in particular and the community in the City Health Center in Bangkinang City